Woman's Struggle Against Oppression in Colette Film - Nur, Citra Junia; Ariani, Setya; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
ABSTRACTOppression is an action that aims to gain benefits for oneself while the other party is harmed. Oppression in Colette film can be seen in how the male character controls the female character. This research aims to identify the types of oppression and the female character’s struggles against oppression as depicted in the film. Moreover, the researcher examines oppression and the struggles in Colette film using Iris Marion Young’s theory. Further, the researcher used a qualitative research method and feminist perspectives. The result of this research showed there are three types of oppression that the female character experienced, they are exploitation, powerlessness, and violence. Besides, the woman’s struggle of the female character that the researcher found are the freedom of speech and economic rights.